COVID-19: Counseling With Bereaved Parents. (July 2021) - Bradley, Loretta; Hendricks, Bret; Noble, Nicole; Fox, Tara
In an era with death from COVID-19 increasing daily, this article emphasizes grief and loss issues of which the family counselor should be aware. Specifically, this article focuses on the needs for family counselors to be aware of grief and loss issues experienced by a parent whose child died from COVID-19. Within this article, grief literature is reviewed. Counseling techniques are highlighted and resources for bereaved parents are provided.